2005
DOI: 10.1302/0301-620x.87b1.15199
|View full text |Cite
|
Sign up to set email alerts
|

Severity of hip dysplasia and loosening of the socket in cemented total hip replacement

Abstract: We have assessed the long-term results of 292 cemented total hip replacements which were performed for developmental dysplasia of the hip in 206 patients. The mean age of the patients at operation was 42.6 years (15.9 to 79.5) and most (202) were women. The severity of dysplasia was graded according to both the Crowe and the Hartofilakidis classifications. A 22.25-mm Charnley head was always used and the acetabular components were inserted with cement into the true acetabulum. Bone grafting of the acetabulum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 24 publications
3
42
0
4
Order By: Relevance
“…In this study, there was a high rate of postdysplastic hips (38 %) and a signifi cantly larger number of these were among the revised cases (p = 0.001). This signifi cantly compromised the survival of the prosthesis in spite of the fact that the vast majority of these cases were those of the Hartofi lakidis type I which should result in survivorship comparable to primary osteoarthritis 22 . Moreover, Castoldi et al used ABG I in 49 postdysplastic hips (31.2 %) and they did not report inferior results for that group of patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was a high rate of postdysplastic hips (38 %) and a signifi cantly larger number of these were among the revised cases (p = 0.001). This signifi cantly compromised the survival of the prosthesis in spite of the fact that the vast majority of these cases were those of the Hartofi lakidis type I which should result in survivorship comparable to primary osteoarthritis 22 . Moreover, Castoldi et al used ABG I in 49 postdysplastic hips (31.2 %) and they did not report inferior results for that group of patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Several classification systems have been used to describe the different types of CHD in adults [1][2][3][4]. However, the reliability of those systems has not explicitly been the focus of attention and their validity has not been, to our knowledge, been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For the classification of congenital hip disease (CHD) in adults various systems have been proposed [1,12,16,17]. The Hartofilakidis et al classification system, initially published in 1988, relies on intraoperative findings to describe the hip pathology encountered during the operation [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies showed [7][8][9][10][11][12][13] that THR in the setting of developmental dysplasia has higher rates of complications and inferior outcomes when compared with THR performed for primary osteoarthritis. Moreover, the results depend on the severity of dysplasia, and patients with lower grades of dysplasia tend to have better results than patients with higher grades of dysplasia [14], so interpretation of long-term results after THR requires detailed information about the degree of dysplasia.…”
Section: Introductionmentioning
confidence: 99%